2010
DOI: 10.1111/j.1468-1331.2010.02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic gray matter loss in Parkinson’s disease without dementia

Abstract: Our results suggest that corticolimbic degeneration occurs in non-demented patients with PD, and extensive involvement of the limbic and posterior cortical regions as well as the frontal cortices is associated with cognitive impairment in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
5
54
0
Order By: Relevance
“…Some of these investigations reported distributed GM reduction in the patients with PD. [34][35][36] A few studies found more local reduction of GM in PD, although the regions were inconsistent across the studies. 37,38 In addition, some reports showed no differences between PD and controls.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these investigations reported distributed GM reduction in the patients with PD. [34][35][36] A few studies found more local reduction of GM in PD, although the regions were inconsistent across the studies. 37,38 In addition, some reports showed no differences between PD and controls.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies have identified extensive gray matter volume loss in temporoparietal and prefrontal areas in PD-MCI compared with controls, 28 others detected small density reductions in the precuneus, primary motor, parietal cortex, 29 in addition to occipital areas, 30 or cortical thinning in focal frontal regions. 31 However, the small sample sizes, lack of consistent criteria for defining MCI, and the use of different measures of atrophy are among the parameters that could account for inconsistent findings among previous studies.…”
Section: Vertex-wise Comparisons Of Cortical Thickness Between (A) Comentioning
confidence: 99%
“…Investigations employing structural MRI analysed by visual inspection, region of interest and whole brain voxel based morphometry (VBM) methods have reported grey matter atrophy associated with dementia in PD in the basal ganglia, medial temporal and limbic areas, as well as other cortical regions 4–8. Some studies defining a single ‘non-dementia’ group of PD subjects have reported atrophy in the medial temporal lobe,4 7–10 amygdala,7 frontal regions6 10 and cerebellum 11. In contradistinction, others have found no significant atrophy in PD without dementia 12–15.…”
Section: Introductionmentioning
confidence: 99%
“…However, small sample size and lack of consistent criteria for defining cognitive impairment complicate the interpretation of these structural imaging results and perhaps explain inconsistent findings. Some studies have identified grey matter atrophy in PD-MCI patients in the temporal lobe (including the hippocampus and parahippocampus), frontal regions and cerebellum, relative to healthy individuals or PD patients without cognitive impairment 10 19 20. In contrast, other studies have reported either no or unreliable grey matter changes in PD-MCI compared with controls or PD-N 5 21 22.…”
Section: Introductionmentioning
confidence: 99%